2013
DOI: 10.5146/tjpath.2013.01221
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of bcl-2, c-myc, survivin and tumor grade in synovial sarcoma

Abstract: Tumor grade was the most significant prognostic parameter in this study. The grade IIa group (with less than 10 mitoses in 10 HPF, without necrosis) had a better prognosis than both the grade IIb and III groups. The grade IIb group was closer to grade III regarding the prognosis. Bcl-2 and c-myc (nuclear and/or cytoplasmic) immunohistochemical positivity had prognostic value but this finding has to be confirmed by large series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Indeed, c-Myc is upregulated in a number of sarcomas including leiomyosarcoma, osteosarcoma, chondrosarcoma, synovial sarcoma, ARMS and EwS. [32][33][34][35][36][37][38][39] Myc is a basic helix-loop-helix zipper transcription factor that regulates its target genes by binding to a conserved E-box DNA sequence CACGTG. 40 It mainly exerts its effect on the cell cycle by transcriptionally activating cyclins and CDKs or by repressing p15 INK4b , p21 CIP1 , and p27 KIP1 .…”
Section: Alterations In Cell Cycle Regulatorsmentioning
confidence: 99%
“…Indeed, c-Myc is upregulated in a number of sarcomas including leiomyosarcoma, osteosarcoma, chondrosarcoma, synovial sarcoma, ARMS and EwS. [32][33][34][35][36][37][38][39] Myc is a basic helix-loop-helix zipper transcription factor that regulates its target genes by binding to a conserved E-box DNA sequence CACGTG. 40 It mainly exerts its effect on the cell cycle by transcriptionally activating cyclins and CDKs or by repressing p15 INK4b , p21 CIP1 , and p27 KIP1 .…”
Section: Alterations In Cell Cycle Regulatorsmentioning
confidence: 99%
“…erefore, the apoptosis of hepatocellular carcinoma cells was substantially enhanced in the DEN + IVIG group in contrast to the DEN + NS group. In addition, the Bcl-2 family indirectly controls cell-autonomous death by interacting with the proto-oncogene c-myc [24].…”
Section: Discussionmentioning
confidence: 99%
“…MYC expression in synovial sarcoma was previously reported to be inversely related to disease-free survival. Demir et al 45 showed that cases with MYC nuclear positivity of more than 5% of cells had a decreased survival time compared to negative cases, while Shen et al 46 demonstrated that MYC protein expression in more than 5% of cells correlated with a higher relapse rate. In the latter paper, MYC positivity was not statistically significantly correlated with Ki67 (MIB1) proliferation index.…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al. 45 showed that cases with MYC nuclear positivity of more than 5% of cells had a decreased survival time compared to negative cases, while Shen et al. 46 demonstrated that MYC protein expression in more than 5% of cells correlated with a higher relapse rate.…”
Section: Discussionmentioning
confidence: 99%